How the Liberation Day Announcement is Shaping the Global Trade Order: From Free Trade to Fair Trade Agreements - Ojo, Marianne (Journal of Finance Research Letters, 2025)
It may be assumed that all of the United States’ trading partners were impacted by the recent “Liberation Day” announcement – an announcement which constitutes “two distinct tariff actions” – as will be highlighted in this paper. However, despite previous concerns of being targeted by their free trade agreement (FTA) partner, Canada and Mexico – as would have been or should be expected, have been exempted from the tariff imposition. As well as addressing factors which have contributed to the shift from free trade to increasingly and predominantly protectionist stances and most likely, fair trade practices, this paper is aimed at highlighting and explaining the rationales behind the recent historical developments – as well as highlighting those factors that have triggered the build up to the Liberation Day Announcement of the 2nd April 2025. It is remarked that “Trump’s reciprocal tariff doctrine, holds foreign countries accountable”. Against this backdrop of discontent with World Trade Organisation’s dispute resolution mechanisms, which will be further elaborated on, in the paper, the immediate and possible long term impacts of the Announcement, will be considered. As well as exploring the reasons for recent developments – by way of reference to historical developments and data, the paper also considers the underlying frameworks governing the calculations of recent tariff rates and hikes. Whilst there are arguments regarding the validity of such calculations, or whether the current scenario justifies the basis for implementing “national emergency measures”, what can be regarded as an emergency response can be determined through a consideration of underlying and contributory factors. If negotiations, and more specifically, bilateral negotiations, take place as hoped, between those countries impacted by the Liberation Day Announcement, financial stability across global markets is expected to be restored. However, if retaliatory measures follow – with an escalation of trade wars, possible repercussions should be cause for concern. The global trading system is still recovering from the recent crisis which was largely uncontrollable – hence, it is more likely (and hoped) that the recent market turbulence and volatilities will be short term.
Keywords: Deregulation; Dispute resolution mechanisms; Financial stability; Free trade agreements; Manufacturing; Monetary policy; Protectionism; World Trade Organisation

A path to paperless trade: analysing the legal gaps and economic benefit of adopting or maintaining a legal framework that takes into account the UNCITRAL Model Law on Electronic Transferable Records (MLETR) - Committee on Trade and Investment (CTI) (Asia-Pacific Economic Cooperation, 2025)
Keywords: Asia and the Pacific; DIGITAL TECHNOLOGY; ELECTRONIC COMMERCE; UN Convention on the Use of Electronic Communications in International Contracts (2005); UNCITRAL Model Law on Electronic Commerce (1996); UNCITRAL Model Law on Electronic Transferable Records (2017)

Internationality overreach in the interpretation of uniform private law conventions: the Contra Proferentem rule and the CISG - Kryla-Cudna, Katarzyna (International and comparative law quarterly, 2025)
This article argues that the rule of contra proferentem is not applicable to international sales contracts governed by the United Nations Convention on Contracts for the International Sale of Goods (CISG). It further argues that the common recognition of the rule of contra proferentem under the CISG is an instance of a broader phenomenon which it calls ‘internationality overreach’. ‘Internationality overreach’ is the tendency to project onto the provisions of a uniform private law instrument doctrines and concepts which are inaccurately presumed to constitute universally recognised principles of private law or the ‘common core’ of various legal systems. This article demonstrates that internationality overreach disrupts the goals underpinning the harmonisation of commercial law in two ways: first, it undermines uniformity in the application of international conventions; and, second, it leads to outcomes that fall short of the agreement reached by the Contracting States during the drafting process. While this article focuses on the CISG, the argument developed in this article is of equal relevance to other uniform private law conventions which follow the principle of autonomous interpretation.
Keywords: INTERNATIONAL SALE OF GOODS; INTERNATIONAL TRADE LAW; UN Convention on Contracts for the International Sale of Goods (1980)

Intra-Africa trade and the need to rethink the neo-liberal approach - Ngwu, Franklin; Ojah, Kalu (Transnational Corporations Review, 2024)
Notwithstanding past trade reforms, trade in Africa and particularly intra-Africa trade, remain dismal. Africa has even created economic communities, fitted with monetary, fiscal, and socio-political anchors, by way of various Regional Economic Communities (RECs) – now reflected by the African Continental Free Trade Area (AfCFTA). Whilst these have yielded marginal benefits, the persistence of low intra-Africa trade calls into question their suitability. Focused on the realities of institutions targeted by these reforms and Africa's context – i.e., weak linkages between institutions, high informality, and low social capital – we posit that reforms have not elicited the hoped-for high intra-Africa trade because of their near total reliance on the neo-liberal approach, which neglects Africa's context. Drawing on Africa's sociology and new institutional economics, we use a conceptual institutional analysis to evolve a political economy based framework that suggests potential solutions: Linking the formal sector that currently underpins economic/trade policies to the informal institutions that are reflective of Africa's norms, values, cultures and expectations (the informal sector), and scaling up production; via the cooperatives production model, strategic procurement mandates, and effectuation of continental transportation infrastructure network, are our recommended pathways to reversing the current dismal intra-continental trade.
Keywords: Africa; Africa's sociology; Growth and trade policies; Institutional economics; Intra-Africa trade

Beyond free trade in raw materials: Reconciling international trade rules with planetary boundaries - Kuppuswamy, Chamundeeswari; Boklan, Daria (The Extractive Industries and Society, 2024)
International trade rules enshrined in agreements like the General Agreement on Tariffs and Trade (GATT) promote free trade, with exceptions for environmental protection. This paper explores the tension between these rules and Earth Systems Science's concept of planetary boundaries, which define environmental tipping points beyond which humanity faces irreversible harm. We analyse GATT's provisions, particularly Article XI's prohibition on trade restrictions and Article XX's exceptions, through the lens of planetary boundaries. Our analysis argues that current interpretations of these articles are inadequate to address the environmental impact of raw material trade. We further examine the concept of permanent sovereignty over natural resources, which grants states autonomy over resource exploitation and trade. We posit that planetary boundaries are not a restriction on sovereignty but a call for modifying state trading behaviour and consequently how international trade rules is structured and interpreted. This analysis demonstrates the complexity of transforming the legal landscape necessary for a global just energy transition, a response to climate change that requires aligning international trade with environmental sustainability.
Keywords: Climate change; GATT Art. XX; No-harm principle; PSNR; Planetary boundaries; WTO trade rules

Facilitating Trade through Rules of Origin: A Consideration of the African Continental Free Trade Area - Okoroma, Blessing Ijeoma (University of Calgary, 2024)
Rules of origin play a pivotal role in free trade agreements. Apart from serving as a tool to distinguish goods by determining the nationality of a product, rules of origin have the capacity to increase trade relations or deter it. Of course, it is the hope of any viable state to increase profitable trading relations, and if rules of origin can help with that, it becomes expedient to fully understand how these rules of origin operate. In Africa, we see rules of origin being implemented amongst the Regional Economic Communities (RECs), but this has come with many struggles. In fact, low intra-African trade can be narrowed down to complex rules of origin regimes deployed in regional agreements in Africa. As of date, the major RECs have each implemented different rules of origin, leading to the co-existence of conflicting rules of origin across Africa. This non-uniformity in the rules of origin regimes in Africa has resulted in low continental trade in Africa. As such, these RECs have not yielded the expected increase in intra-African trade. With the creation of the African Continental Free Trade Area (AfCFTA), which currently doubles as the latest and largest FTA in Africa, it is expected that better rules of origin will be deployed to mitigate the existing intra-African trade deficits. This thesis thus deploys a doctrinal approach in determining whether AfCFTA’s rules of origin are positioned to achieve greater intra-African trade. Consequently, this thesis uncovers some lapses in AfCFTA’s rules of origin and calls for harmonization of all the rules of origin in Africa and recommends a possible amendment to Article 19 of the Agreement establishing AfCFTA to accommodate the intended harmonization.
Keywords: African Continental Free Trade Area; Free Trade Area; Rules of Origin

African Continental Free Trade Area and Regional Trade in ICT and Digital Technologies - Adams, Kweku; Attah-Boakye, Rexford; Yu, Honglan; Chu, Irene; Mali, Dafydd (Journal of International Management, 2024)
This study examines the impact of the African Continental Free Trade Area (AfCFTA) on regional trade in the Information and Communication Technology (ICT) and Digital Technologies (DT) sector across 43 African countries from 2014 to 2021. Employing the augmented gravity model and confidence-level estimations, it highlights AfCFTA's mediating role in enabling ICT&DT trade on the continent. Using hierarchical regression analysis of a panel dataset comprising 5,160 observations, the findings imply that trade openness and productive capacities not only facilitate trade in the ICT&DT sector but also result in positive spillover effects across various economic sectors. This study contributes to the international business literature by refining the application of the gravity model to capture the need for sector-specific analyses to unpack institutional dynamics and dis-enablers of trade. It identifies AfCFTA as a pivotal yet underexplored element in the global trade landscape, highlighting its potential as Africa seeks a more prominent role on the global stage. The research stresses the significance of digital empowerment and policy reforms to maximise the benefits of regional integration under AfCFTA.
Keywords: AfCFTA; ICT and digital technologies; Regional trade; Trade enablers; Trading bloc

Multilateralism and Bilateralism in International Trade - Aro, Gilbert; Nwosu, Chiedozie; Ngene, Innocent; Nnadi, Samuel (African Journal of Politics and Administrative Studies, 2024)
The contemporary international system is dominated by international trade. Therefore, it is the fundamental and critical aspect of international economic relations. The study investigated the how African states participate in common bilateral and multilateral trade relations. Its core objective is to study whether trade barriers have been made less cumbersome among the participating countries in African continental region. Common trade and international trade justify the essence of globalization. The wave of globalization has necessitated the flux of multilateralism and bilateralism among the participating nations in the international trade. Methodologically, the study adopted comparative theory of international trade. Its method of data collection is documentary method and analyzed through interpretive studies. As the international trade continues to take the centre stage in the international economic relations; States continue to engage in multilateral and bilateral trade relations. The operations of Transnational Corporations (TNCs) and Multi-national Corporations (MNCs) as non-state actors also engage in multilateral and bilateral agreements with the host states. Several agreements led to the establishment of General Agreement on Tariff and Trade (GATT) and World Trade Organization (WTO) remains conspicuous products of multilateralism and bilateralism in the international trade in the recent time. African Continental Free Trade Area (AFCFTA) is a multilateral agreement enacted by fifty-four members of the African Union (AU) in 2019 to boost trade relations among them. Its core benefit is to facilitate free trade and removal of trade barriers in the region Therefore, this study is set to examine the advantages and impacts of AFCFTA and other multilateral and bilateral agreements in Africa and the world at large.
Keywords: AfCFTA; Bilateralism; International Trade; Multilateralism; Trade agreements; WTO

Nigeria-China Relations and Economic Development - Chiedozie, Nwosu; Aloh, Ngwuta; Ibiam, Okechukwu; Nwankwo, Felix; Ikpolo, Gabriel; Iwuala, Harrison (African Journal of Politics and Administrative Studies, 2024)
This work explored the dynamics of Nigeria-China relations from the political and economic points of view between 1999-2023. The primary concern of this paper is to discern the extent Nigeria-China relations is mutually beneficial and how Nigeria can stand to gain more if the relationship is properly aligned to Nigeria’s national interest. The central argument of this work is that Nigeria stands to gain more from China than from the West bearing in mind the fact that over one hundred years of Africa’s relationship with the West has been largely exploitative and disadvantageous. In this regard, the research employed both primary and secondary sources of data collection. The primary sources relied on first-hand information gathered from the Chinese Embassy as well as key actors within the Nigeria External Affairs Ministry and Key Informant Interviews on experts in Nigeria-China relations. The secondary sources relied on already existing information from libraries, text books, journals and the internet. The theoretical framework employed is the Complex Interdependence Theory. The conclusion drawn from this work is that Nigeria-China relations have not fully developed to the extent of being more beneficial to Nigeria economically and politically. What currently subsists is that China is gaining economically more in terms of trade to Nigeria’s disadvantage. However, politically and socio-culturally, the two countries are mutually benefiting due to various diplomatic protocols and cultural exchanges. The study recommended among others that Nigeria must strive to develop her techno-industrial export-oriented base to ensure more symmetric beneficial relationship with China.
Keywords: Bi-Lateral Relations; China; Development; Economic Development; Nigeria

The African Continental Free Trade Area (AfCFTA): Taking stock and looking ahead for international business research - Debrah, Yaw A.; Olabode, Oluwaseun E.; Olan, Femi; Nyuur, Richard B. (Journal of International Management, 2024)
The establishment of the African Continental Free Trade Area (AfCFTA) has opened new avenues of research interest in International Business and International Management. However, scholarly work in this fledgling area of research has been disparate and often lacking in the assessment of core international business implications of the emergence of the AfCFTA on member states as well as non-member states. This is because, as yet, no systematic attempt has been made to explore the AfCFTA in the context of IB research, or project future IB research directions. Hence, in this paper, using the PRISMA method we have systematically identified the current published research and scholarly work on the AfCFTA and provided a robust picture of the current state of knowledge and available literature on the AfCFTA while at the same time outlining potential areas for future international business research.
Keywords: AfCFTA; African Continental Free Trade Area; Informal cross-border trade; International business; Regional economic communities (RECs); Systematic literature review

How can the rule of law under the WTO framework ensure sustainable fishery governance through fishery subsidies? A study from the perspective of special and differential treatment - Bai, Jiayu; Wu, Yuting (Heliyon, 2024)
Background Considering the declining situation of sustainability in global marine fisheries, World Trade Organization (WTO) members successfully concluded the Agreement on Fisheries Subsidies(AFS) after 21 years of negotiations in 2022. As an the integral part of these negotiations, special and differential treatment (SDT) provisions provide developing countries with special rights and developed countries with the possibility to treat developing countries more favorably than other WTO members. Objective This study analyzed the role of SDT for fisheries subsidies in ensuring sustainable fishery governance by the rule of law, as well as the reflection of SDT under the AFS, to explore whether SDT can support sustainable fishery governance under the WTO framework. Methods This study is primarily based on official data and critical legal studies and used normative analysis and historical analysis to expose the essence of the SDT issue in the AFS as a political game in the legal form. Results The practical challenges in the implementation of SDT may affect the compliance willingness of member states. To overcome the obstacles, such as ambiguity and inefficiency, that impede the legalization process of sustainable global marine fishery governance, it is necessary to emphasize the value of SDT for the common interests of the WTO members in marine fisheries legislation. This will benefit the developing countries, especially the small island developing states, in the short term; and the common interests of developed and developing countries in the long term. Policy implications SDT facilitated the consensus between the developing and developed countries on issues such as illegal, unreported, and unregulated fishing subsidies and overfishing subsidies. However, current SDT practices have deviated from the original intention of the fairness and democratic approach of global marine fisheries governance, which should take into consideration the specific situation of developing countries.
Keywords: Agreement on fisheries subsidies; Overfishing; Rule of law; Special and differential treatment; Sustainable fishery governance; World Trade Organization

Property in goods and the CISG - Maier-Lohmann, Till (Recht der internationalen Wirtschaft / Abhandlungen zum Recht der internationalen Wirtschaft, 2024)
Keywords: CONTRACTS; INTERNATIONAL SALE OF GOODS; UN Convention on Contracts for the International Sale of Goods (1980)

An In-Depth Analysis of Choice of Law Rules in Consumer Contracts: A Focus on the African Continental Free Trade Area - Fiattor, Ethel (Journal of Law, Society and Development, 2023)
Choice of law is a perplexing concept due to the importance of party autonomy, the diversity of connecting factors, and the variety of different contractual issues. The problem of choosing a governing law is complicated in consumer contracts by industrialised mechanisms depriving consumers of negotiation rights. The core mandate of the African Continental Free Trade Area (AfCFTA) is to establish a single market for goods and services associated with the free movement of legal persons for economic integration. This objective requires a harmonised consumer protection policy to resolve the diverse consumer protection regimes applicable in state parties within AfCFTA member states. This policy should provide suitable consumer protection mechanisms generally and in the context of choice of law specifically. Implementing a draft competition policy bestows a legitimate mandate on the AfCFTA to negotiate a continental framework on consumer protection as both fields of law complement each other to safeguard consumer rights in cross-border trade. This article argues the dynamics of providing adequate choice of law rules on consumer contracts to inform suitable mechanisms on consumer interest within the AfCFTA. The article discusses the abuse of choice of law clauses in consumer contracts, affecting consumers’ rights in cross-border contracts within the AfCFTA. It suggests a harmonised consumer protection policy to regulate and mitigate these clauses. The article also examines trends in Global North jurisdictions like the European Union to inform a context-specific institutional framework for the AfCFTA’s choice of law rules.
Keywords: AfCFTA; Applicable law; Choice of law; Consumer protection; Economic integration; Harmonisation; International law; ZLECAf

The significance of a forum selection agreement as an indicator of the implied choice of law in international contracts: a global comparative perspective - Okoli, Chukwuma Samuel Adesina (Uniform Law Review, 2023)
Where the parties to an international contract fail to specify the choice of law, a forum selection agreement is one of the most, if not the most, significant factors to consider in implying the choice of law in many international, supranational, regional instruments, and national jurisdictions. However, it is an ill-defined, notoriously complex, and hotly debated issue as to the weight that should be attached to a forum selection agreement in implying the choice of law. Hence, this article is devoted to discussing this topic from a comparative perspective, in order to propose a guide to global uniform criteria. To achieve this, the article covers all relevant international, regional, and supranational instruments, and selected legal systems in Africa, Asia, Australasia, Europe, the Middle East, and North and South America. The legal systems compared include those from the global North and global South, including common law, civil law, and mixed legal systems. The article’s core proposal is that an exclusive forum selection agreement should be a key factor in implying the choice of law. However, except in such cases as where a forum is chosen on a neutral basis, there should be a general requirement of corroboration with at least one other factor of significance. The aim of the proposal is to contribute to greater uniformity, predictability, and certainty in the global community in this field of law.

Addressing the Legitimacy Crisis of Investment Arbitration Through its Harmonization with World Trade Organization Law - Seifi, Seyed Jamal; Veis Karami, Mahdi (Public Law Researsh, 2023)
International investment law is facing a legitimacy crisis, in which to tackle, substantial efforts are being made in structural and procedural areas. The first step to overcoming this crisis is identifying the roots of it. The lack of a dynamic balance between public and private interests is one of the main factors creating this legitimacy crisis in this legal system.[1] This paper focuses on the changes in the investment arbitration jurisprudence to create this balance. The findings of this paper can explain one of the convergence points of international trade and investment law. Such a claim is based on the evolution of international trade law in facing a similar legitimacy issue and the structural-procedural approach of this legal system in balancing public and private interests as an ultimate solution to the crisis.[2] From this perspective, one of the major factors in creating a legitimacy crisis in both legal systems is the dominance of the paradigm for preference of private interests; and one of the convergence points of international trade and investment law has been to replace it by accepting the paradigm of creating a dynamic balance between competing goals.[3] This paper examines this convergence in arbitral jurisprudence.IntroductionIn recent years, the legitimacy crisis of the regime of international investment law and, as a result, the investor-state dispute settlement system has been one of the most important and controversial topics in the academic environment and the practice of states consequently, serious efforts in various fields to tackle this crisis have begun. According to this paper, choosing an arbitration mechanism modeled on international commercial arbitration to resolve disputes between host states and foreign investors can be evaluated as a wrong and hasty action that, regardless of its factors and contexts, has changed the nature and function of this system over time.[4] It should be noted that the main factor in such consequences is how this dispute resolution system is used which, contrary to the accepted model, always puts the host states in a "respondent" position in possible future disputes and, as a result, disrupts the balance expected in any international dispute settlement system. On this basis, the confrontation of the host state's sovereign competence in ensuring public interests with the foreign investors’ ability to challenge this competence is brought into the spotlight: currently, within the regime of international investment law, host states have only responsibilities and obligations in contrast to extensive and exclusive rights and privileges recognized for foreign investors, and this can be considered as the most important factor disturbing the said balance. The main issue in this field is to analyze the role of the investment arbitral tribunals in creating such a balance. In this regard, the authors, by focusing on the nature of investment treaties, and the relations between the parties in investment disputes and with emphasis on the general legal regime governing international investment, consider creating a dynamic balance between public and private interests to be the key to solving the crisis. They emphasize that; As long as the rights and obligations of the parties to the dispute are based on imbalanced grounds, the change in nature of the disputes and the function of the system -as the main roots of this legitimacy crisis - will remain. In this remark, it is very important to focus on the two-sided nature (public-private) of the relationships established in the framework of investment treaties. The relationship between the host state and the foreign investor is created within the framework of investment treaties and in light of fundamental differences from purely private relationships in international commercial arbitration.[5] Note that any dispute arising from this relationship is affected by its inherently public nature governed by public international law.[6] Thus, a purely private attitude towards these relations does not seem viable. As Ian Brownlie has stated in the case of SME v. the Czech Republic, it can lead to ignoring some of the basic elements of the relevant investment treaty.[7] In other words, the right and duty of the host state in protecting and promoting public interests is a fundamental part of this relationship, and any indulgence of it leads to a serious disruption of the mentioned balance through which the system's legitimacy will be the first victim.It is clear that the main task of any dispute resolution system is to create such a balance, and on this basis, and compared to the WTO dispute resolution system, the role of the investment tribunals in this process is discussed. This jurisprudential convergence is in line with the goal of strengthening the legitimacy of the international investment law system as a whole.Based on the above, the first part of this paper focuses on the process of establishing the ISDS in international investment law and its characteristics, the factors of the crisis of legitimacy are analyzed with an analytical approach, while also explaining the nature of investment treaties and explaining the general legal regime governing international investment. Furthermore, the lack of a dynamic balance between public and private interests is emphasized as the main cause of the crisis. In the second part, while comparing the two legal systems of international trade and investment with a similar crisis of legitimacy, we will examine the interaction of investment arbitration with the WTO's jurisprudence in facing this crisis through a case study of several investment arbitral awards. [1]. David Gaukrodger, “The Balance between Investor Protection and the Right to Regulate in Investment Treaties: A Scooping Paperˮ, OECD Working Paper on International Investment 2017/02, at 4.[2]. Nicholas DiMascio & Joost Pauwelyn, “Non-Discrimination in Trade and Investment Treaties: Worlds apart or Two Sides of the Same Coin?”, AJIL, Vol. 102, No.1, (2008), at 89.[3]. Jurgen Kurtz and Sungioon Cho, “Convergence and Divergence in International Economic Law and Politics”, EJIL, Vol. 20, No. 1, (2018), at 187.[4]. Benedict Kingsbury & Stephan W. Schill, “Public Law Concepts to Balance Investor's Rights with State Regulatory Actions in the Public Interest - The Concept of Proportionalityˮ, In Schill Stephan W., International Investment Law and Comparative Public Law (UK: Oxford University Press, 2010) at 76. [5]. Crina Baltag, “Reforming The ISDS System: In Search of a Balanced Approach?ˮ, Contemporary Asia Arbitration Journal, Vol. 22, No. 2, (2019), at 285.[6]. Ibid.[7]. Andreas Kulick, “Sneaking Through Backdoor – Reflections on Public Interest in International Investment Arbitrationˮ, Arbitration International, Vol. 29, No. 3, (2013), at 438.
Keywords: Crisis of Legitimacy; International Investment Law; Investor-State Dispute Settlement; WTO; World Trade Organization

Legal harmonisation of non-tariff barriers of regional economic communities as a catalyst to the realisation of the African continental free trade area - Achancho Etagha Epse Abia, Elisabeth (University of KwaZulu-Natal, 2023)
Legal harmonisation is an integral aspect of regional integration and the desire to promote regional and sub-regional economic integration in Africa is exemplified by the establishment of the African Continental Free Trade Area (AfCFTA) in 2018. The 2012 decision of the AU to create the CFTA by 2017 was reiterated in Aspiration two of Agenda 2063. The legal harmonisation of non-tariff barriers has been a vital instrument in the achievement of EU economic integration and the Organisation for the Harmonisation of Business Laws in Africa (OHADA). The study seeks to critically examine the theoretical and conceptual underpinnings of regional integration and legal harmonisation of non-tariff barriers by the AU and RECs. It also analyses the current political, economic, and legal reinforcements to regionalism in Africa and practices needed to advance intra-regional trade within the framework of Agenda 2063. This was done by evaluating the key legal frameworks of the AU (the Abuja Treaty, the Constitutive Act of AU, 2007 Protocol on relations between AU and RECs and Agenda 2063) with the aim of identifying best practices, gaps and impediments pertinent to strengthening Agenda 2063 CFTA. At the end of the study, the abilities of three selected RECs (SADC, COMESA and EAC) were assessed to drive home the AfCFTA. This was done by identifying flaws in existing treaties of RECs, while advancing a model of legal harmonisation of NTBs between them. It was found out that the AU and RECs have not vigorously considered the significance of legal harmonisation in their integration agendas. This resulted in the lack of unambiguous and concrete provisions for the legal harmonisation of NTBs in their guiding policies. Where some attempts are evident, such as in the EAC, they have been implemented unsatisfactorily with lack of a compliance mechanism. This study contended that if legal barriers to free trade are not eliminated, even if all other barriers were to be removed, the effective realisation of the AfCFTA would still be hindered. Hence, this study recommends the principles of direct applicability and direct effects of regional laws to addressing the legal harmonisation challenge underscored. Iqoqa Ukuvumelanisa okusemthethweni kwezithiyo ezingakhokhiswa intela kuyisici esibalulekile sokudidiyelwa kwesifunda kanye nesifiso sokugqugquzela ukuhlanganiswa komnotho wesifunda kanye nesifunda esincane e-Afrikha sibonakala ngokusungulwa kweNdawo Yezwekazi Lase-Afrikha Yokuhweba Ngokukhululekile (i-AfCFTA) ngowezi-2018. Isinqumo sowezi-2012 se-AU sokwakha i-CFTA ngowezi-2017 saphindwa Esifisweni Sesibili soHlelo- 2063. I-CFTA iphinde ibe wuhlelo olubalulekile oHlelweni-2063 futhi impumelelo yayo ibalulekile. Ucwaningo luhlose ukuhlola ngokujulile izisekelo zethiyori nezomqondo zokuhlanganiswa kwesifunda kanye nokuvunyelaniswa kwezomthetho kwezithiyo ezingakhokhisi yi-AU kanye nama-REC. Iphinde ihlaziye ukuqiniswa kwamanje kwezepolitiki, ezomnotho, kanye nezomthetho kuzwelonke e-Afrikha kanye nezinqubo ezidingekayo ukuze kuthuthukiswe ukuhwebelana kwangaphakathi kwesifunda ngaphakathi kohlaka loHlelo-2063. Lokhu kwenziwa ngokuhlola izinhlaka zomthetho ezibalulekile ze-AU (iSivumelwano sase-Abuja, UMthetho-sisekelo we-AU, 2007 Protocol on relationship between AU and RECs and Agenda 2063) ngenhloso yokuhlonza izindlela ezingcono kakhulu, amagebe kanye nezithiyo ezihambisana nokuqinisa uHlelo-2063 CFTA. Ekupheleni kocwaningo, amakhono ama-REC amathathu akhethiwe (i-SADC, i-COMESA kanye ne-EAC) ahlolwa ukuze aqhubekisele phambili i-AfCFTA. Lokhu kwenziwa ngokuhlonza amaphutha ezivumelwaneni ezikhona zama-RECs, ngenkathi kuthuthukiswa imodeli yokuvumelana okusemthethweni kwama-NTB phakathi kwawo. Kwatholakala ukuthi osopolitiki base-Afrikha abazange bayicabange indlela eqinile yokuhlanganisa umnotho wesifunda, nakuba indlela enjalo yaphakanyiswa abasunguli besifunda sase-Afrikha. I-AU kanye nama-REC awazange acabangele ngamandla ukubaluleka kokuvumelana kwezomthetho ezinhlelweni zawo zokuhlanganisa. Lokhu kuholele ekuntulekeni kwezinhlinzeko ezicacile nezibambekayo zokuvumelana ngokusemthethweni kwama-NTB kuzinqubomgomo eziqondisayo. Lolu cwaningo lwagomela ngokuthi uma izithiyo ezingokomthetho zokuhwebelana ngokukhululeka zingaqedwa, ngisho noma zonke ezinye izithiyo zizosuswa, ukufezeka ngempumelelo kwe-AfCFTA kusazothikamezwa. Ngaphakathi kwalokhu kwangemuva, lolu cwaningo luncoma izimiso zokusebenziseka okuqondile kanye nemiphumela eqondile yemithetho yesifunda ukuze kubhekwane nenselele yokuvumelana kwezomthetho egcizelelwe.
Keywords: Common External Tariff; Direct Effect; Legal harmonisation

The Autonomy Doctrine in the Law of Letters of Credit and Demand Guarantees in Libya, Egypt and England: A Comparative Study - Mukhtar Elhouderi, Tajeldin Eissa Saleh (University of Leicester, 2023)
Letters of credit and demand guarantees play a prominent role in financing international trade. They provide assurance of payment and security for the performance of contractual obligations and have been described as the ‘lifeblood’ of international commerce. Autonomy is the central principle for the instruments of letters of credit and demand guarantees. Under the autonomy principle, the bank’s undertaking to pay for the beneficiary ought to be independent of the diversity of other relationships arising from the underlying contract. In spite of the autonomous nature of these instruments, in certain cases, the national laws will recognise some exceptions or limitations that restrict the application of the doctrine of autonomy. Exceptions such as fraud, nullity, and illegality will allow the national courts to interfere and override the autonomy doctrine by considering other matters, even those concerning the underlying contract. Furthermore, the exceptions of unconscionability or abuse of rights have an effective role in providing deep solutions, especially with regard to the problem of abusive calls for demand guarantees. The autonomy principle is recognised under Libyan commercial law but has yet to form the subject of serious academic literature covering its legal aspects. This study, in part, aims to fill that gap and will examine the extent to which legal aspects govern the principle of autonomy and its exceptions under Libyan law with reference to the new Libyan Commercial Code. A comparison of the laws in England, Libya, and Egypt will be conducted to examine how legal matters concerning autonomy and its restrictions in their laws are addressed. Furthermore, consideration will be given to the experience of Singapore, particularly with regard to the unconscionability and nullity exceptions. The results of this study will consider many different exceptions to autonomy and suggest that fraud is not the only exception to autonomy and that it is not imperative that all exceptions in letters of credit be equally applied to demand guarantees.
Keywords: Commerce international; Comparative study; Contractual obligations; Egypt; England; International Trade; International commerce; Letter of credit; Letter of guarantee; Lettre de crédit; Lettre de garantie; Libya; Obligation contractuelle

African Principles on the Law Applicable to International Commercial Contracts - Neels, Jan (UJ Press, 2023)
This booklet contains the first draft of the envisaged African Principles on the Law Applicable to International Commercial Contracts. The proposal could be used by national legislators on the continent and African economic integration organisations, particularly the African Union, in, respectively, domestic legislation and regional or supranational laws of a soft or binding nature. The existence of a reliable transnational legal infrastructure in respect of international commercial law, including commercial private international law, is a prerequisite for investor confidence, inclusive economic growth, sustainable development, and the ultimate alleviation of poverty on the African continent. The instrument may contribute to sustainable growth on a long-term basis. The regulation of private international law of contract is essential to the further development of the African Continental Free Trade Area. Jan L Neels is professor of private international law and director of the Research Centre for Private International Law in Emerging Countries at the University of Johannesburg.
Keywords: African principles; International commercial contracts

Trade between China and 45 African countries: does the Gravity Model matter? - Ondja'A Abeng-Abe, Christian Johan; Ebissemitie Kisso, Eunice (Revue d’Études Sino-Africaines, 2023)
The population of Africa and that of China put together amounts to a little over one-third of the world's total. The theoretical justification of the gravity model is applied to analyze the factors influencing bilateral trade between China and African countries using the panel data regression technique, covering the period between 2002 and 2021 and with special consideration for the income level of the African countries. Empirical results and estimates reveal that the economic size as well as the population of trade partners positively affect China’s trade with 45 African countries. The positive impact that distance has on trade is inconsistent with previous research. We conclude from the analysis that the factors affecting trade between China and African countries are, namely, the size of the population, the economic size represented by the GDP, and the distance between the countries. The indication of effects on the trade sector is important, and the sensitivity of the potential product to distance and countries varies considerably, giving a revealed comparative advantage. African countries should diversify their exports and improve their trade diplomacy.
Keywords: Africa; China; Gravity Model; Panel data regression; Trade

Legal texts on trade facilitation: comparative analysis of the World Trade Organisation and the African Continental Free Trade Area - Shumba, Willie (University of South Africa, 2022)
Trade agreements are a common feature in international economic law as they govern trade relations between states. These agreements are anchored by a firm foundation of the requisite legal provisions to support trade. In this regard, the World Trade Organisation (WTO) and the African Continental Free Trade Area (AfCFTA) have each developed their own legal texts that acknowledge the significance of trade facilitation and would, when implemented, facilitate the movement of goods and services across international borders. The thesis was a comparative analysis of the legal texts on trade facilitation of the WTO and the AfCFTA whose aim was to identify the resemblances and divergences between the two. The WTO has a broader mandate of global trade and ensures that trade amongst its members is conducted in conformity with global rules. On the other hand, the AfCFTA is a trade agreement that has been negotiated by African member states pursuant to the political vision of the African Union (AU), and within the confines of WTO, specifically Article XXIV of GATT 1994. This research was therefore undertaken against the backdrop of these seemingly contradicting circumstances. The central research question for the study concerns the differences and similarities between the legal texts on trade facilitation of the WTO and the AfCFTA. The study was qualitative involving a desktop review of primary and secondary sources of data. Among others, the thesis finds that the AfCFTA complies with the strategic goals of the AU, and at the same time, complements the multilateral trading system of the WTO. The thesis concludes that while there are certain similarities, the legal texts on trade facilitation of the WTO and the AfCFTA are different. The inherent dissimilarities in the texts are not contrary to the principles of the WTO. The thesis contributes to scholarly literature in trade facilitation with respect to both the AfCFTA and the WTO. It also identifies new areas for further studies and provides the necessary groundwork. The study recommends some improvements that can be made to the respective legal texts on trade facilitation.
Keywords: AfCFTA; AfCFTA Agreement; African Continental Free Trade Area; Comparative analysis; Customs union; Free trade area; GATT; General Agreement on Tariffs and Trade; Global trade; International Trade; Legal texts; Multilateralism; Regional Economic Community; Regional Trade Agreements (RTAs); Regionalism; Trade Facilitation Agreement (TFA); Trade agreement; Trade facilitation; World Trade Organization

Trade facilitation through border enforcement of Intellectual Property Rights: issues, concerns and possible remedies - Hossain, Syed Saifuddin (Macquarie University, 2022)
In the present era of rapid globalisation, countries are intrinsically integrated with each other by way of international trade to ensure optimal utilisation of their resources. Trade facilitation is now recognised as a key driving factor in determining export competitiveness of a country. Customs administrations, the frontier border agency responsible for regulating import and export of legitimate goods, are increasingly faced with the challenge of intellectual property rights (IPR) infringement. In addition to national governments, various international organisations have devised guidelines and tools to facilitate and empower Customs agencies in their fight against IPR infringement. In particular, the multilateral Agreement on Trade Related Aspects of Intellectual Property Rights (TRIPS) of the World Trade Organization (WTO) articulates a prescription for border enforcement of IPRs in Articles 51-60. In this backdrop, this thesis attempts to answer a very fundamental question: What are the implications of ‘Border Measures’, specified under the WTO TRIPS Agreement, for facilitating international trade? To this end, it critically examines the concepts of trade facilitation, TRIPS and IPR protection to highlight the links that connect them and the missing links that need to be established. Obligations to protect IPR under national and international laws are also scrutinised. Research shows that efforts by WTO, World Customs Organization (WCO) and World Intellectual Property Organization (WIPO) have been instrumental in this context. While policy planning at the national level should be the first priority, commitment by the advanced economies to support their less developed counterparts through technology transfer (TT) is of paramount importance. The thesis suggests that TRIPS-plus provisions, if implemented arbitrarily by developed countries, have the potential to undermine the interests of countries with resource constraints. In this context, the thesis analyses the effects and implications of the Trans-Pacific Partnership (TPP) and the Trans-Atlantic Trade and Investment Partnership (TTIP) agreements, and the Revised Kyoto Convention (RKC) for the border protection of IPRs. The thesis investigates the socio-economic impacts of IPR infringement and articulates strategies to be adopted and applied at individual, collective, business and government levels to stop trade and use of IPR infringed goods. Drawing on the analysis of the relevant WTO Articles, scrutiny of various border measures put in place by national governments and international bodies, and current state of play under the Doha Development Round (DDR), the thesis puts forward a set of short and long term policy recommendations for all relevant stakeholders. These inclusively include: (i) strengthening risk management procedures; (ii) cooperation and coordination at national and international levels; (iii) awareness raising initiatives; (iv) establishing advanced technologically driven border enforcement system; (v) empowering Customs with effective administrative authority; (vi) IP related technical capacity building within the Customs and business community; (vii) technology transfer to LDCs from developed countries; and (viii) LDC friendly dispute settlement process under the WTO.
Keywords: Border protection; Customs; IPR; Intellectual property; Intellectual property infringement; Intellectual property rights; Trade facilitation

Soil protection and legal aspects of international trade in agriculture in times of climate change: The WTO dimension - Ruppel, Oliver C. (Soil Security, 2022)
Soils are essential for food security and the right to food. But where is the connect between soil, trade in agriculture and the rules of the World Trade Organization (WTO)? While the WTO is not an environmental protection agency (as per its initial design at least), existing WTO rules fail to make agricultural trade patterns sustainable when it comes to the medium of soil. Notwithstanding, trade policy is of growing importance to soil protection, biodiversity preservation, deforestation, land degradation and desertification. Soil is key in this regard not only because it is the world's second-largest carbon sink after the oceans. Unsustainable trade in agricultural commodities should increasingly be seen in light of an industrial transition to increased climate neutrality and decarbonisation. This in turn should be guided by the leitmotiv – in times of climate change - to place soil protection for sustainable food security at the centre of any economic policy, also in terms of the rules on international trade in agriculture under the WTO.
Keywords: Climate change; Decarbonisation; Food security; Soil protection; Trade in agriculture; World trade law

The Economics of Trade, Innovation and the Technology Revolution - Tharwat, Ismaeel (Université Paris-Saclay, 2022)
Cette thèse étudie principalement l'impact du commerce international sur l'innovation, avec un accent particulier sur les pays en développement. Elle couvre également l'impact des retombées commerciales sur les inégalités de genre. Le chapitre 1 présente un aperçu de la littérature économique théorique et empirique récente traitant de l'effet de la concurrence des importations sur les résultats liés à l'innovation. Ce chapitre est divisé en quatre sections. Tout d'abord, un historique des brevets et des marques déposées en tant qu'indicateurs d'innovation est présenté. Deuxièmement, les mécanismes théoriques qui sous-tendent l'impact de la concurrence des importations sur l'innovation sont discutés. Troisièmement, une revue de la littérature des études empiriques récentes sur le commerce et l'innovation est résumée. Enfin, une analyse empirique est menée pour examiner l'impact de la concurrence des importations chinoises sur l'innovation, mesurée par l'activité de dépôt de brevet, dans les pays en développement.Le chapitre 2 est un exercice empirique qui examine l'impact de la concurrence des importations chinoises sur l'innovation, en utilisant une nouvelle mesure qui est le dépôt de brevet. L'étude utilise un ensemble de données de panel de 1995 à 2018 sur plus de 100 pays en développement. Le modèle empirique corrige l'endogénéité en utilisant une approche de variable instrumentale qui permet d'identifier la part du développement dû aux importations chinoises dans d'autres pays en développement. Les principales estimations trouvent un effet global décroissant de la concurrence des importations sur l'activité de dépôt de brevet. Les résultats de la variable instrumentale sont particulièrement robustes pour les demandes de brevet, mais pas pour les enregistrements. Cela suggère que la concurrence des importations affecte négativement les nouvelles innovations locales de produits ou de services dans les pays en développement.Enfin, le chapitre 3 aborde la question de l'impact des retombées du commerce international sur les normes d'égalité de genre. La majorité des études existantes documentent l'effet des épisodes de libéralisation sur les inégalités de genre. Celui des acteurs commerciaux, en revanche, a été largement ignoré. L'inégalité de genre au sein d'un pays est-elle affectée par ses partenaires commerciaux? Nous avons examiné cette question dans cet article en adoptant un modèle spatial du commerce entre 123 pays sur la période 1997-2013. Nous utilisons l'indice d'inégalité de genre pour capturer les tendances globales sur le genre au sein d'un pays. Nous avons ensuite désagrégé les échanges commerciaux au niveau produits afin d'identifier un canal technologique. Les résultats montrent que des normes d’égalité de genre plus élevées à l'étranger se répercutent, via les importations de produits de moyenne, haute technologie et minéraux, sur des normes d'égalité de genre plus élevées au niveau national. Ces résultats suggèrent qu'une révolution technologique affecte les entreprises, les ménages et les gouvernements en ayant un impact sur l'autonomisation des femmes.
Keywords: Brevets; Brevets d'invention; Economie du genre; Economie internationale; Gender Economics; Innovation; International Trade; Marques commerciales; Marques de commerce; Patents; Technologie; Technology; Trademarks; Économie de marché; Études sur le genre

Digitalization, institutions and new venture internationalization - Brieger, Steven A.; Chowdhury, Farzana; Hechavarría, Diana M.; Muralidharan, Etayankara; Pathak, Saurav; Lam, Yan Tong (Journal of International Management, 2022)
This study examines the effect of digitalization on the internationalization of new ventures and further investigates the influence of a home country’s presence of institutional voids and digital infrastructure on the extent of internationalization by new ventures, with the prediction that a home country’s institutional voids and a weak digital infrastructure strengthen the positive relationship between new ventures’ digitalization and internationalization. Applying multilevel modeling on a sample of more than 6000 entrepreneurs from 62 countries the study offers empirical support for these predictions. The findings are robust to alternative specifications. Entrepreneurs using the internet to sell their products and services are more likely to focus on customers in foreign markets when they face institutional voids and a lack of digital infrastructure in their home countries. The study contributes as follows: From a theoretical view, it provides a better understanding of the boundary conditions of the digitalization-new venture internationalization linkage. From a practical perspective, the findings of the study suggest the complementary roles of institutional voids and digital infrastructure at home to help entrepreneurs grow domestically and facilitate their internationalization.

Local Content Requirements in WTO Law: Between Free Trade and the Right to Development - De Lima Figueiredo, Natalia (Maastricht University; Universidade de São Paulo, 2022)
In the international arena, there is a strong rhetoric against a type of industrial policy measure called local content requirements (LCRs). They are often characterised, especially by developed countries, as protectionist measures. However, under certain circumstances, LCRs can have a central role in a country’s development process. Indeed, both developed and developing countries use them to boost their economies. Despite this developmental aspect of LCRs, WTO (World Trade Organization) rules restrict their use. The WTO Agreement, however, has a development dimension and WTO law is supposed to be read in light of the wider corpus of international law. The right to development, in turn, is a principle rooted in core human rights treaties, is consolidated in several instruments of soft law nature and could potentially play a role in the interpretation of WTO provisions. In this scenario, the thesis investigates if it is possible to further a development-oriented interpretation of WTO rules affecting LCRs so that those measures that incorporate genuine development goals are not considered a violation of WTO rules.
Keywords: Development; Free Trade; Human rights; Local content requirements (LCRs); WTO; World Trade Organization

Sanitary and phytosanitary measures as barriers to trade : a South African perspective - Joubert, Biandri (North-West University, 2022)
Sanitary and phytosanitary (SPS) measures are measures aimed at the protection of human, animal and plant life and health, within World Trade Organization (WTO) Member territories, from the risks associated with the introduction and spread of pests and diseases into such territories through trade. The WTO, through its Agreement on the Application of Sanitary and Phytosanitary Measures (WTO-SPS), guides the application of sanitary and phytosanitary measures and provides a set of guiding principles, rights and obligations applicable to Member States. Dispute resolution through the processes of the WTO is available to Members on a Member to Member level within a defined scope and on specific terms. Private parties who operate within the SPS chain at a national level, whether involved in import or export or neither, are dependent on solutions to barriers or disputes available to them through national legislation. In the absence of an enabling legal framework to facilitate aspects of trade such as certainty and continuity in standard setting, the basis of measures taken in science, transparency and legal recourse to resolving barriers or disputes arising, private parties are vulnerable to fluctuations in, for example, their country’s disease-free status. Private parties are also vulnerable to losing relevance as trading partners in periods of ongoing SPS events and to the loss of trust that trading partners have in the country’s ability to trade safely. These are matters that affect private parties who do not have legal recourse to the WTO dispute resolution procedures which are well within WTO concern as they are directly related to the purpose of SPS measures, the principles, rights and obligations on which they are based. Given the importance of agriculture and the increasing inseparability of international rights, obligations and principles in a field of WTO law such as SPS, the importance of a national legislative framework in as far as being the translator of such rights, obligations and principles into legally enforceable rights, obligations, principles, processes and procedures is significant. The rights, obligations, and principles of SPS measures apply to all products, processes and procedures that are within the scope of the agreement and may include at least 36 chapters of the harmonised tariff book. It is necessary to consider also that international trade, national trade and the associated rights, obligations, and principles of the WTO-SPS agreement interact with the social, political, and economic realities of the country within the countries to which the agreement applies. Therefore, researching some of the persistent challenges experienced by the red meat industry in South Africa prone to negative trade-related consequences during and after the outbreak of a notifiable disease, provides insight into the perception of the ability of the legislative framework to provide solutions to these consequences. This research applies a mixed methodology approach whereby qualitative research by means of semi-structured interviews was combined with doctrinal legal research and a quantitative content analysis using Rprogramming. The qualitative research focused on the role of legislation and the perspectives of selected actors in the red-meat industry, specifically in reference to the foot-and-mouth-disease (FMD) outbreaks and subsequent loss of disease-free status since 2019. The doctrinal legal analysis and content analysis focused on the SPS-related legislative framework. The combination of these methods provides a multi-perspective analysis of SPS measures as barriers to trade from a South African perspective and contributes to the mixed-methods turn in legal studies. The objective of this research is to identify and explore persistent challenges to the prevention and resolution of barriers or disputes connected to sanitary and phytosanitary (SPS) measures in the South African context. Ultimately, this research recommends potential practical solutions to the identified challenges with specific focus on SPS-related barriers or disputes that are beyond the strict terms of dispute resolution available through the World Trade Organization (WTO).
Keywords: AfCFTA; Barriers to trade; CADA; CAQDSA; Content analysis; Dispute resolution; FMD; NTB; OIE; Qualitative research; Rstudio; SADC; SPS; Sanitary and phytosanitary measures; WTO

The use of blockchain technology in international commercial transactions, with specific reference to secured payments in international contracts of sale - Muza, Chido Teclar Mitchel (University of Johannesburg, 2022)
Please refer to full text to view abstract.
Keywords: Blockchains (Databases); Commercial law; Electronic funds transfers; Export sales contracts.; Foreign trade regulation

The (Domestic) Enforcement of AU International Economic Law Instruments: Exploring the Desirability of Direct Effect - Simo, Regis Yann (The Emergent African Union Law: Conceptualization, Delimitation, and Application, 2021)
This chapter deals with the principle of direct effect as applied in European Union law and explores its suitability in the enforcement of African Union (AU) legal instruments, notably those setting up the African Continental Free Trade Area (AfCFTA). What motivates the issue of direct effect is the noted reticence of African countries to litigate trade matters between themselves despite the existence of provisions of regional trade treaties creating courts of justice which give standing to Member States. Therefore, it surveys the avenues through which natural and legal persons can uphold their rights stemming from AfCFTA treaties thus contributing to treaty interpretation and increasing security and predictability. Currently, the AfCFTA Dispute Settlement Protocol, modelled after the WTO, does not allow such a possibility, contrary to rights acquired by natural and legal persons before some African Regional Economic Communities (RECs) courts. Nevertheless, this chapter finds that carving out access of natural and legal persons to AfCFTA proceedings may not always work as intended since there are other ways to bypass these obstacles. These loopholes could be the gateway through which direct effect will develop and become a principle of AU law broadly speaking. These gaps further complement this chapter’s suggestions to explore amending the AfCFTA legal instruments, even though its dispute settlement system is yet to be tested, in order to match the standing that natural and legal persons have acquired under the RECs, which, in fine, are building blocs towards achieving the AfCFTA and, eventually, the African Economic Community.
Keywords: AfCFTA; Africa; Direct effect; International Economic Law; International Law; International Trade Law; Regional courts; Regional integration

Soft Law in International Investment Law and Arbitration - Adinolfi, Giovanna (The Italian Review of International and Comparative Law, 2021)
In the more recent decades, international investment law (“iil”) and arbitration have been going through a process of recalibration prompted by both the intensification of cross-border capital flows and the States’ growing concerns over the potential restraints iil may impose upon the pursuit of public interests. The present contribution will pay attention to a specific feature that can be observed within these developments, i.e. the role played by soft law in investment arbitration and, more generally, under iil, also with a view to assessing the impact on the formation of binding international law of instruments formally devoid of normative force within the international legal order. After an introduction (Section 1), the contribution is articulated into four sections. Section 2 will first define the field of investigation. The case law of investment tribunals and the treaty practice under the more recent iia s will be then explored as to the reliance on soft law instruments for the purposes of settling procedural (Section 3) and substantive issues (Section 4). Some final remarks will close (Section 5).

Post award arbitral tribunal's mandate under the UNCITRAL Model Law and national laws based thereon - Al Hyari, Omar Hisham; Al Ani, Abdullah Rabee (Heliyon, 2021)
The UNCITRAL Model Law on International Commercial Arbitration provides for the extension of the mandate of the arbitral tribunal post issuance of the final award for the issuance of correction, interpretation, additional award, and remittance of the award back to the arbitral tribunal to remove grounds for challenging the award. Using a doctrinal approach, this paper examines the deviations of the national laws of adopting jurisdictions from the Model Law in regards to this extended mandate, and evaluates the improvements and drawbacks in these deviations. Mainly, the findings of this paper are that, of the many deviations, the positive changes are those that provide comfortable and lenient default provisions for the benefit of inexperienced parties, and since correction, interpretation, additional award, and remittance are useful provisions that are designed to help self-rectify the arbitral process, without adversely delaying it, then the changes that increase the efficacy of these provisions are welcomed. On the other hand, unnecessary deviations are seen as drawbacks that hinder the harmonization of national arbitration laws aimed at by the Model Law. The adopting jurisdictions shall be limited to those acknowledged as such by the UNCITRAL.
Keywords: Additional award; Arbitrage; Arbitragem; Arbitration; Arbitrators' mandate; Award; Correction; Interpretation; Model Law jurisdictions; UNCITRAL Model Law

The impact of multilateral trade agreements on intra-regional trade : the case of SADC and ECOWAS - Osarumwense, Uwakata Yvonne (University of South Africa, 2021)
This study examines the comparative impact of multilateral trade agreements on intra-regional trade in the Southern African Development Community (SADC) and the Economic Community of West African States (ECOWAS) regions in Africa. Annual data was gathered from 2000 to 2018 and dynamic panel data and econometric techniques were used to control for individual country characteristics, endogeneity, serial correlation, heteroscedasticity and interdependencies between the countries in each region. Two estimations were done, one using the tariff measures of multilateral agreements, the second using non-tariff measures of multilateral agreement. The results of the empirical analysis show that the SADC region has a slight edge over ECOWAS in terms of technological progress and investment, especially in trade infrastructure. However, the ECOWAS levels of employment and economic growth are higher than those in the SADC region. These differences further translate into differences that drive intra-African trade in these regions, and how they relate to the role of multilateral agreements in intra-African trade in each of these regions. While technology and investment are key drivers and enhancers of intra-African trade in SADC countries, economic growth and employment stand out as key enhancers of intra-African trade in ECOWAS, especially where multilateral agreement is represented by tariff measures. This study reports that when non-tariff measures are used to represent multilateral agreements, export trade costs, in addition to investment and technology, are the key drivers of intra-African trade in SADC countries. For ECOWAS, under non-tariff measures of multilateral agreements, only economic growth drives intra-African trade.
Keywords: Commercial treaties; Customs unions; Institutional environment; Intra-African trade; Investments; Multilateral agreement; Panel data estimation; Tariff and non-tariff trade barriers

The Impact of Trade Openness and Foreign Direct Investment on Economic Welfare in sub-Saharan Africa - Adegboye, Folasade Bosede; Adesina, Olumide Sunday; Olokoyo, Felicia Omowunmi; Ojeka, Stephen Aanu; Akinjare, Victoria Abosede (International Journal of Financial Research, 2021)
The sub-Saharan African region is characterized by a high relative degree of openness to trade. The region is also identified with increased inflows of foreign investments with no significant welfare improvement. Economic development emphasizes that the lack of domestic investment in the developing economies could be boosted by trade openness and inflow of Foreign Direct Investment (FDI) for impactful enhancement of capital formation. In this article, the impact of trade openness and foreign capital inflow on economic welfare was examined on a sub-regional analysis for sub-Saharan Africa. The study also appraised the effect of openness to trade and FDI inflow on the region's economic welfare. The data for 30 countries from 2000 to 2018 were collected and analyzed, with the Generalized Least Square (GLS) technique to fit the model developed. The study showed that openness to trade has a significant impact on economic welfare for all sub-Saharan Africa regions, while FDI is only significant for the Western sub-region. Hence, the study recommends that the government of the countries in the sub-Saharan Africa region should boost trade openness to enhance efficiency in productivity, and improve industrial development.
Keywords: Economic Welfare; Foreign direct investment; Sub-Saharan Africa; generalized least square; sub-regional analysis; trade openness

Experimenting with international commercial dispute resolution - Erie, Matthew S; Bookman, Pamela K (AJIL Unbound, 2021)
In this essay, we describe the overlapping phenomena of new legal hubs (NLHs), international commercial courts, and arbitral courts. We survey their impact on the law and geopolitics of international commercial dispute resolution, identifying key issues these new dispute resolution institutions raise. While the rise of international commercial courts spans authoritarian and liberal states, Western and Asian states, common law and civil law traditions, it also highlights and builds upon regional differences. We question the assumption that the establishment of new courts is always consistent with an increase in the rule of law, particularly in non-democratic states. We close with thoughts about the potential influence and future role of these institutions. Some of the procedural innovations discussed here may lead to shifts in international commercial dispute resolution for years to come, but the question of whether there is sufficient demand for these new institutions lingers.

Historical and comparative perspectives on trade union regulation with specific emphasis on the accountability of trade unions to their members - Greenhalgh, Bradley Paul (Stellenbosch University, 2020)
How do members hold their own trade unions accountable in South Africa? What legal mechanisms, if any, are available to assist union members in receiving adequate representation and service from their unions? This study approaches these questions through a comparative and historical examination of the regulation of the union member relationship in the UK, USA and the RSA. The study commences with an examination of what unions do, how they function and what benefits potentially accrue to their members, while the role played by unions in utilising collectivisation to offset the bargaining power of employers is demonstrated. The need for organised labour, by society in general, but South Africa specifically, is brought into sharp relief. This is, however, offset by the examination of 25 constitutions of broadly representative South African trade unions, where the lack of proper regulation of the union-member relationship is brought to the fore. This already means the common law and current judicial approach that is so reliant on the interpretation and implementation of trade union constitutions to address union-member disputes is unsuitable, certainly in those instances where the constitution is either silent or ambiguous, or where the nature of the relationship between the union and its member(s) mimics that of the constantly present imbalance of power and influence between employers and employees. The comparative examination of union accountability is undertaken against the backdrop of the common historical phases of proscription, acknowledgement/assimilation, and readjustment of and towards trade unions. The historical and contemporary regulation of the union-member relationship in South Africa is examined in the same way. The study demonstrates that purely statutory regulation of the union member relationship by means of punitive provisions and inter-union self-regulation measures are not feasible. A series of possible legal mechanisms – that draw from the comparative examination – are suggested, even though they are to be utilised in a collective (rather than individual) way. Even these suggestions, however, are subject to the challenges of cost-effectiveness, accessibility and efficiency of enforcement by (the) average union member(s). Three proposals are made to foster improved union member accountability: Firstly, the use of section 103A of the LRA by the Registrar so as to place unions that meet the appropriate criteria under administration, in order to restore accountable functioning and elevate the interests of the member(s) over that of the officials of the union; secondly, the introduction of a duty of fair representation – to be administered by the CCMA – to hold both union and employer accountable to members, and; thirdly, in conjunction with the first two proposals, the use of a package of further measures (and an associated information campaign), such as bolstering the financial/institutional capacity of the Registrar’s office, compelling the inclusion of accountability clauses within union constitutions, and minor amendments to the LRA with regard to balloting, reporting/transparency (and the enforcement thereof). If implemented, the expected outcomes are improved labour relations, increased accountability and professionalisation of trade union administration, a realignment of the employer-union divide and elevating the awareness of union member rights and concomitant obligations on trade unions – all of which are of critical importance in South Africa’s post-Marikana society.
Keywords: Labor union members; South Africa; Trade union accountability; Union security

An economic and legal analysis of trade measures against illegal, unreported and unregulated fishing - Ma, Xuechan (Marine Policy, 2020)
Illegal, unreported and unregulated (IUU) fishing threatens the ability of the aquatic systems to continue providing vital ecosystem services and essential food resources. Most of the existing economic analysis on IUU fishing is conducted from the perspective of IUU fishing vessels rather than that of States. This paper seeks to fill this gap and concludes that trade measures against IUU fishing are cost-effective for the international community, as the IUU fishing has reached such a substantial scale that the total harm or loss caused is estimated to be greater than the total abatement costs required. Meanwhile, from a legal point of view, trade measures against IUU fishing might have more tensions with international trade law than with the international law of the sea. This paper draws on relevant GATT and WTO jurisprudence for guidance to eliminate such tensions. Two other comprehensive solutions to ensure legal compliance of trade measures against IUU fishing include taking such measures on a cooperative basis and making use of the standard-setting process through competent international organizations or conferences such as the FAO.
Keywords: Economic analysis; IUU fishing; International trade law; The law of the sea; Trade measures

The African Continental Free Trade Area: Toward a New Legal Model for Trade and Development - Kuhlmann, Katrin; Agutu, Akinyi Lisa (Georgetown Journal of International Law, 2020)
International trade law is at a turning point, and the rules as we know them are being broken, rewritten, and reshaped at all levels. At the same time that institutions like the World Trade Organization (WTO) face significant change and a global pandemic challenges the rules of the market, Africa’s new mega-regional trade agreement, the African Continental Free Trade Area (AfCFTA), is emerging as a promising framework for redesigning international economic law. As this Article will argue, the AfCFTA presents a new normative approach to trade and development that is positioned to rewrite the rules in a more inclusive and equitable way and, over time, possibly affect global trade well beyond the African continent.Historically, trade and development have been linked through the framework of Special and Differential Treatment (S&D), which has been a central feature of the WTO and is increasingly shaping regional trade agreements (RTAs) as well. Although the connection between trade and development is more important than ever before, traditional S&D is not positioned to deliver on broader priorities of social and economic development in the current international climate. Fortunately, as this Article will argue, Africa’s approach under the new AfCFTA sets the stage for a needed refresh of S&D. While the AfCFTA incorporates traditional aspects of S&D, it also includes elements of a forward-looking, rules-based approach to further economic and social development, advancing the Sustainable Development Goals (SDGs). This new dimension of S&D holds great potential for promoting integration through trade, representing the needs of a diverse group of countries in the rulemaking process, and reshaping international economic law more broadly to generate positive development outcomes. This Article begins with an assessment of the AfCFTA as an alternative model for trade and development law, evaluating the agreement in the historical and evolving context of S&D and examining its role in shaping a new normative approach to S&D. The AfCFTA, we argue, represents a shift from using S&D as a largely defensive trade approach to one that positions S&D as an affirmative tool for achieving sustainable development through the design and implementation of the rules of trade themselves, while still maintaining flexibility for countries that need it. This new approach may finally replace the old trade paradigm of the ”haves and have nots” with a system in which trade rules can be designed to benefit all. Although the AfCFTA is still at an early stage and will have to overcome formidable challenges, this Article provides an initial assessment of the AfCFTA’s proactive new model in the context of the substantive areas of law identified as next-stage (Phase II) negotiating priorities: intellectual property rights (IPR), investment, and competition law. The Article’s comparative assessment draws upon the laws of African nations, African and international RTAs, and other proposals for international legal reform. Finally, the Article looks to the future, positing that the AfCFTA could be the best legal instrument available to break the stalemate in international rulemaking, design new trade law approaches to pressing issues like global health and food security, and close the loop between trade rules and development goals, including the seventeen SDGs. As the AfCFTA is rolled out and implemented, it could have a profound impact on trade and development law, reshaping the rules for Africa and perhaps the world as well.
Keywords: AfCFTA; African Continental Free Trade Area; International Economic Law; International Trade

Trade in Services in the African Continental Free Trade Area: Prospects, Challenges and WTO Compatibility - Simo, Regis Yann (Journal of International Economic Law, 2020)
This article engages with the recently adopted agreement for the African Continental Free Trade Area (AfCFTA) in the area of services. While services trade had heretofore stood at the queue of African trade pacts, the AfCFTA breaks new grounds by negotiating goods and services concurrently, signalling a paradigm shift and a commitment to a deeper integration of the continent. Upon Members’ implementation of the Protocol on Trade in Services, whose aim is to establish a single market in services, the region will be the largest economic integration agreement ever concluded since the birth of the World Trade Organization (WTO). This paper sets out to analyse the provisions of the Protocol and how they contribute to achieving the objective of attaining a single market where services (alongside goods, people and capital) move unrestricted.

The regulation of international commercial arbitrators - Loreto Ilhao Moreira, João (University of Oxford, 2020)
International commercial arbitration has established itself as the main dispute resolution mechanism for international commercial disputes. This increased visibility has drawn attention to arbitrators’ public role, leading to a well-established general perception that arbitrators are bound to special obligations, such as the duty to be independent and impartial or the obligation to assure that arbitral proceedings are not abused to achieve nefarious goals. Despite this general acknowledgement, little attention has been paid to the mechanisms that ensure that arbitrators adhere to these obligations. In particular, there has been limited analysis of the underlying mechanisms that incentivise the production and enforcement of professional norms in this field. This thesis argues that the particulars of the arbitration market largely explains why the evolution of the regulation of international arbitrators has not matched those of other professions. At the same time, it will argue that those same particularities create incentives for several actors, most notably the arbitral community itself, to step in and occupy this regulatory vacuum. In particular, it explores the notion that the market strategies employed by arbitrators, arbitral institutions and other members of the arbitral community have the production of professional norms as a by-product. It further explores how the arbitral market tends to create an environment where compliance with professional norms is rewarded, leading, at the same time, the arbitral community to work as a network that promotes adherence to professional norms through mostly informal sanctions.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration (international law); Arbitration market; Dispute Resolution; International commercial arbitrators; Regulation